Eliminating leading corrections to scaling in the three-dimensional O(N)-symmetric model φ4: N = 3 and 4 - Hasenbusch, Martin (Journal of physics. A, Mathematical and general, 2001)
We study corrections to scaling in the O(3)- and O(4)-symmetric ϕ4 model on the three-dimensional simple cubic lattice with nearest-neighbour interactions. For this purpose, we use Monte Carlo simulations in connection with a finite-size scaling method. We find that a finite value of the coupling λ* exists for both values of N, where leading corrections to scaling vanish. As a first application, we compute the critical exponents ν = 0.710(2) and η = 0.0380(10) for N = 3 and ν = 0.749(2) and η = 0.0365(10) for N = 4.